The Impact of The Court Map in the Field of Advocacy - Rushiti, Ana (Indonesian Journal of Advocacy and Legal Services, 2022)
The rule of law operates in accordance with the law, focusing on the equality of citizens before the law and the prohibition of the arbitrary power of the executive (Government). Justice reform is a mechanism that made it possible for citizens to increase their trust in justice. Justice reform was a mechanism that we had not heard before and it is important in this paper to mention the causes and consequences of justice reform by balancing them to understand its positive and negative sides. Judicial reform has mostly affected judges and prosecutors, but also lawyers in court cases as well and the public had an important role to denounce any judge or prosecutor who had given court decisions in violation of the law but also cases of corruption of judges or prosecutors. In this paper it is very important to address two very important principles sanctioned by the European Convention on Human Rights. the second is a trial within a reasonable time by analyzing court decisions and the importance of respecting deadlines by the courts for a speedy and effective justice. A new innovation taken from the countries of the European Union was the new court map that does not brought a few debates in our country and how the new court map will affect the economy of Albanians given that Albania is a developing country.